Zn-Ni-Co trimetallic carbonate hydroxide nanothorns branched on Cu(OH)2 nanorods array based on Cu foam for high-performance asymmetric supercapacitors - Liu, Ying; Cao, Xueying; Cui, Liang; Zhong, Yuxue; Zheng, Rongkun; Wei, Di; Barrow, Colin; Razal, Joselito M.; Yang, Wenrong; Liu, Jingquan (Journal of power sources, 2019)
Here we report the development of a high-performance electrode material composed of Zn and Ni co-substituted Co carbonate hydroxide (ZnNi-Co2(CO3)(OH)2) nanothorns branched on Cu(OH)2 nanorods array (Cu(OH)2@ZnNi-Co2(CO3)(OH)2), which are grown directly on copper foam current collector. The electrode materials are obtained by a simple in situ oxidation reaction and a hydrothermal strategy. The as-obtained Cu(OH)2@ZnNi-Co2(CO3)(OH)2 electrode exhibits significantly enhanced electrochemical performance with a high specific capacitance (2746 F g−1 at 1 A g−1), and extraordinary cycling stability (maintained 95.61% of the initial capacitance after 6000 cycles at 20 A g−1), which are much superior to those of Cu(OH)2, Cu(OH)2@ Co2(CO3)(OH)2, Cu(OH)2@Ni-Co2(CO3)(OH)2, and bare ZnNi-Co2(CO3)(OH)2 nanospheres electrodes. Additionally, the Cu(OH)2@ZnNi-Co2(CO3)(OH)2 nanorods array can also be utilized as the positive electrode to fabricate an asymmetric supercapacitor device with an active carbon negative electrode, realizing a high cell voltage of 1.5 V and the energy density of up to 34.75Wh kg−1 at a power density of 375 W kg−1. The excellent electrochemical properties can be credited to the three-dimensional hierarchical core-shell architecture. [Display omitted] •Hierarchical Cu(OH)2@ZnNi-CoCH nanorods array is fabricated on 3D Cu foams.•The materials are obtained by an oxidation reaction and a hydrothermal strategy.•Cu(OH)2@ZnNi-CoCH electrode exhibits superb supercapacitive performance.